7Be spatial and temporal pattern in southwest of Europe (Spain): Evaluation of a predictive model. (August 2018) - Chham, E.; Piñero-García, F.; Brattich, E.; El Bardouni, T.; Ferro-García, M.A.
Abstract: This study presents a comprehensive statistical analysis of the cosmogenic radioisotope 7 Be measured in surface air in ten stations over Spain for a 9 years period (from January 2006 to December 2014). Besides the analysis of 7 Be seasonal and inter-annual variability, 7 Be frequency distributions and its correlations with meteorological variables observed in the 10 sampling sites were investigated. The second part of this paper focuses on a feasibility study for the application of the Artificial Neural Networks (ANNs) to predict monthly 7 Be activity concentrations using meteorological variables, PM10 concentrations and the sunspot number as input parameters. Notwithstanding the low correlations found between 7 Be and input parameter, the performance of the ANNs, as evaluated by the relevant statistical parameters, demonstrates their capability to correctly predict 7 Be monthly activities in the 10 Spanish sampling sites. Highlights: 9 years of monthly measurements of 7 Be in 10 sampling sites were investigated. Temporal, spatial, and frequency distribution of the 7 Be activity were treated. The ANN method was proposed to forecast 7 Be activity. The ANN model provides robust forecasts of 7 Be air concentrations for all stations.